Thin and flexible structure having a surface containing a transparent conductive film and method of forming the same

By forming a combination of sparse metal conductive layer and polymer outer coating on the transparent polymer substrate, the problem of ITO prone to cracks on the flexible substrate is solved, and a thinner and more flexible transparent conductive film is achieved, satisfying the new model The demand for electronic devices improves mechanical stability and production efficiency.

CN113383298BActive Publication Date: 2024-12-17EKC TECHNOLOGY INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080011393.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-01-28
Filing Date
2020-01-27
Publication Date
2024-12-17
Estimated Expiration
2040-01-27

AI Technical Summary

Technical Problem

Existing transparent conductive films such as indium tin oxide (ITO) are prone to cracking on flexible substrates, and the deposition process is complex and costly, making it difficult to meet the needs of new portable electronic devices for thinner and more flexible.

Method used

It adopts a bilateral conductive structure, including a transparent polymer substrate and a sparse metal conductive layer, and forms an extremely thin and flexible transparent conductive film through the combination of a polymer outer coating and a protective film, which is suitable for electronic devices such as touch sensors.

Benefits of technology

It realizes the maintenance of high transmittance, low resistance and mechanical stability in extremely thin and flexible structures, extends the service life of the conductive film, reduces production costs, and improves the flexibility and thinness of the electronic device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113383298B_ABST
    Figure CN113383298B_ABST
Patent Text Reader

Abstract

The present invention describes structures having a thin and flexible polymer substrate with a conductive film on each opposing surface, while having high optical transmittance and good optical properties. The structures can have a total thickness of no more than about 30 microns and good flexibility. Processing methods are described that allow very thin structures to be coated by providing support through a coating process. The structures are demonstrated to have good durability under conditions of accelerated wear designed to test touch sensor use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to transparent structures with transparent conductive surfaces suitable for incorporation into electronic devices having electrodes associated with light transmitting or light receiving structures, such as transparent touch sensors. The transparent structure may have two transparent conductive surfaces on opposite sides of a thin substrate, such as a polyimide layer. The present invention further relates to methods of forming thin and flexible structures with transparent conductive films, which may have transparent conductive films on one or more surfaces of a thin and flexible transparent layer. Background Art

[0002] Functional films can provide important functions in a range of contexts. For example, conductive films can be important for dissipating static electricity when it can be unwanted or dangerous. Transparent conductive films can be used as electrodes. High quality displays can include one or more transparent conductive layers.

[0003] Transparent conductors can be used in several optoelectronic applications, including, for example, touch screens, liquid crystal displays (LCDs), flat panel displays, organic light emitting diodes (OLEDs), solar cells, and smart windows. Historically, indium tin oxide (ITO) has been the material of choice due to its relatively high transparency at high conductivity. However, ITO still has several disadvantages. For example, ITO is a brittle ceramic that needs to be deposited using sputtering, which is a relatively slow and not cost-effective manufacturing process involving high temperatures and vacuum. In addition, ITO is known to be prone to cracking on flexible substrates. Newer portable electronic devices are advancing to thinner formats. Summary of the invention

[0004] In a first aspect, the present invention relates to a double-sided conductive structure comprising a transparent polymer substrate, a sparse metal conductive layer supported on each of a first surface and a second surface of the transparent polymer substrate, and a polymer overcoat layer on each sparse metal conductive layer. In some embodiments, the transparent polymer substrate may comprise a polymer and have a first surface and a second surface, wherein the polymer substrate has an average thickness of no more than about 27 microns, and the polymer in the configuration of the transparent polymer substrate has a transmittance of at least about 88% at 400nm to 750nm and a transmittance of no more than about 15% in the UV spectrum of 330nm to 375nm. Typically, the polymer overcoat layer may have an average thickness of about 10nm to about 200nm. The sheet resistance of each surface of the double-sided conductive structure may not exceed about 120 ohms / square.

[0005] In another aspect, the present invention relates to a method for forming a transparent conductive film, the method comprising:

[0006] forming a sparse metallic conductive layer supported on a first surface of a transparent polymer substrate, the transparent polymer substrate having an average thickness of no more than about 27 microns, wherein the polymer substrate has a second surface supported on a first polymer release film;

[0007] applying a polymeric outer coating layer onto said first sparse metallic conductive layer;

[0008] placing a second polymeric release film on the polymeric outer coating;

[0009] removing the first polymer release film to expose the second surface of the transparent polymer substrate;

[0010] forming a second sparse metal conductive layer supported on the second surface of the transparent polymer substrate; and

[0011] A polymeric overcoat is applied over the second sparse metallic conductive layer.

[0012] In another aspect, the present invention is directed to a transparent conductive film having an average thickness of no more than about 30 microns and comprising a transparent polymer film having an average thickness of no more than about 27 microns, a sparse metal conductive layer on each side of the transparent polymer film, and a polymer overcoat on each sparse metal conductive layer, wherein the polymer overcoat has an average thickness of about 10 nm to about 500 nm. In some embodiments, the transparent conductive film has a sheet resistance of no more than 100 ohms / square on each side, a %TT of at least 89%, a haze of no more than 2.5%, and a b* of no more than about 3.5. In additional or alternative embodiments, the double-sided conductive structure can be assembled into a test structure with an optically clear adhesive (3M, 8146) and a 125 micron thick PET film on each surface and subjected to an accelerated wear test at 85°C and 85% relative humidity for 500 hours, wherein the sheet resistance increases by no more than about 40%. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is a schematic side view of a structure having two sparse metallic conductive layers, one on either side of a thin polymer substrate.

[0014] Figure 2 is formed Figure 1 Schematic flow chart of the process of fabricating the structure.

[0015] Figure 3 is a schematic top view of a pattern of a touch sensor formed by a structure having two stacked patterned transparent conductive layers that form component electrodes of the touch sensor.

[0016] Figure 4is a schematic diagram of the roll-to-roll processing of the double-coated structure described in this article.

[0017] Figure 5 is a flow chart indicating a roll-to-roll process for coating a first side of a substrate used in the Examples.

[0018] Figure 6 is a flow chart indicating a roll-to-roll process for coating the second side of a substrate used in the Examples.

[0019] Figure 7 is a schematic cross-sectional view showing a structure having two conductive surfaces and a hard coat primer layer, which is used to test a sample under 85° C. / 85% RH test conditions.

[0020] Figure 8 yes Figure 7 Graph of R / Ro variation over time for a double-sided conductive structure using a first PI substrate subjected to an 85° C. / 85% RH accelerated wear test.

[0021] Fig. 9 is a schematic cross-sectional view of a structure for performing Xe illumination testing of conductive structures.

[0022] Fig.10 The first PI substrate was used under Xe test conditions. Fig. 9 Graph showing R / Ro variation over time for the double-sided conductive structure shown in FIG.

[0023] Fig.11 is a schematic cross-sectional view showing a structure having two conductive surfaces without a hard coat undercoat layer, which is used to test a sample under the test conditions of 85° C. / 85% RH.

[0024] Fig.12 yes Fig.11 Graph of R / Ro variation over time for a double-sided conductive structure using a first PI substrate subjected to an 85° C. / 85% RH accelerated wear test.

[0025] Fig.13 is a schematic cross-sectional view of a structure for performing Xe illumination testing of conductive structures.

[0026] Fig.14 Under Xe test conditions, Fig.13 FIG. 4 is a graph showing the change in R / Ro over time for the double-sided conductive structure using the first PI substrate.

[0027] Fig.15 is a schematic cross-sectional view showing a structure having two conductive surfaces without a hard coat undercoat layer, which is used to test a sample under the test conditions of 65° C. / 90% RH.

[0028] Fig.16 is a schematic cross-sectional view of a structure for performing Xe illumination testing of conductive structures.

[0029] Fig.17 The second PI substrate subjected to 65°C / 90%RH accelerated wear test was used. Fig.15 A graph showing the R / Ro variation over time of the double-sided conductive structure.

[0030] Fig.18 Under Xe test conditions, Fig.16 FIG. 4 is a graph showing the change in R / Ro over time of the double-sided conductive structure using the second PI substrate.

[0031] Fig.19 The first PI substrate subjected to 65°C / 90%RH accelerated wear test was used. Figure 7 A graph showing the R / Ro variation over time of the double-sided conductive structure.

[0032] Fig. 20 Under Xe test conditions, Fig. 9 FIG. 4 is a graph showing the change in R / Ro over time for the double-sided conductive structure using the first PI substrate. DETAILED DESCRIPTION

[0033] Based on sparse metal conductive layers on opposite sides of a thin transparent polymer substrate selected for specific properties, a transparent conductive structure with a particularly thin profile and durability suitable for electronic devices is designed. The transparent conductive structure can be used for touch sensors. The selected polymer substrate may have a thickness of no more than about 27 microns while providing good visible light transmittance and good UV absorption properties. The UV absorption property provides independent UV-based patterning of the conductive layer on both sides of the substrate. In some embodiments, a flexible polymer substrate with a hard coating polymer protective barrier between the conductive layer and the polymer substrate provides particularly durable properties, as evaluated using an accelerated wear test. A suitable processing method has been developed that makes it feasible to process extremely thin substrates while performing coating on both sides of the substrate. In the process, a suitable protective polymer film can be used and removed at selected steps of the process to provide stable operation and protection of fine structures. The design of the double-coated structure provides independent etching of each surface of the double-sided structure, so that patterns can be introduced (for example) based on touch sensor designs.

[0034] Transparent conductive films, typically based on indium tin oxide, are widely used in touch sensors or other components in electronic devices. Touch sensor designs typically include two conductive elements. One conductive element can be used for one dimension in a reference plane, while a second element can be used for a second dimension in the reference plane to identify touch points along the plane. Therefore, to manufacture a touch sensor, two patterned conductive films are typically used, but additional transparent conductive layers may also be used. In general, touch sensors should be relatively thin, but traditionally each conductive element is associated with a different substrate, which is then assembled into a stack. New products have created a demand for thinner and / or flexible structures. The ability to place two patterned conductive films on a single substrate allows for the formation of thinner and more flexible structures.

[0035] The ability to formulate extremely thin and flexible sensor structures can be an enabling technology for flexible electronic devices. For flexible devices having displays with touch sensors, then the conductive element is transparent. Traditional conductive elements formed from indium tin oxide and similar conductive ceramic oxides are not flexible. The use of sparse metal conductive elements provides the ability to have flexible structures. By placing two transparent conductive films on opposite sides of a single substrate, the thickness is reduced because only a single substrate is required. Moreover, extremely thin substrates have been developed to fit this single substrate. New processing methods have been developed to allow efficient formation of such structures. The ability to form such structures with desired optical and electronic properties at extremely small thicknesses presents significant challenges, and such challenges are met with excellent results as described herein.

[0036] Figure 1 The general structure of a double-sided conductive element in a single form on a core substrate is shown. Figure 1 , the double-sided conductive sheet 100 may include a substrate polymer sheet 102, an optional first hard coating 104, a first sparse metal conductive layer 106, a first outer coating 108, an optional second hard coating 110, a second sparse metal conductive layer 112, a second outer coating 114, an optional first releasable protective film 116, and an optional second releasable protective film 118. The properties of the materials are important for forming a usable structure with proper processing and suitable stability for commercial use in electronic applications. The materials are described in detail below. The sparse metal conductive layer can be effectively provided as a fused metal nanostructured network.

[0037] The formation of a touch sensor can involve separate patterning of the two conductive sides of a double-sided conductive structure. In general, patterning of the conductive layer involves a patterned radiation source, such as a focused laser beam with laser ablation or irradiation through a mask using photolithography using a photoresist. Although patterning can generally be performed with a variety of radiation sources, the desired patterning can be performed with a UV laser for ablation or a photoresist sensitive to UV light. For laser ablation, focused UV light, typically from a UV laser, can be scanned across the surface to define the pattern. For photolithography, UV light is directed through a mask to form a latent image in the photoresist, which is then developed to form a physical pattern. The physical pattern in the photoresist then provides wet or dry etching to transfer the pattern to the sparse metal conductive film. In either case, the two sparse metal conductive layers are typically patterned independently because different patterns participate in different functions of the touch sensor. For efficient processing, it is necessary to pattern both sides so that the patterned side does not affect the other side.

[0038] In order to accomplish double-sided independent patterning, for some embodiments, it may be necessary for the substrate to absorb UV light so that a significant flux of UV light from one side does not reach the other side, where the UV light may change the patterning of the opposite side. On the other hand, the substrate should have a high visible light transmittance. At the same time, at the very small thickness involved, the substrate should have suitable mechanical properties. Depending on the properties of the UV absorbing composition, the absorption of high-energy UV photons may also tend to form reactive species. In order to have suitable durability, the sparse metal conductive layer can protect from any damaging reactive species generated by the patterning process. As described herein, an optional hard coating may be located between the substrate and the sparse metal conductive layer to protect the sparse metal conductive layer. As shown in the examples, the optional hard coating may or may not be used to provide the desired stability of the conductive layer.

[0039] In order to provide the desired UV absorption capability at the desired small thickness while maintaining high visible light transmittance and mechanical durability, a polyimide substrate is exemplified below, but other polymer substrates may be used. A polyimide substrate may be selected to provide good transmittance in the visible spectrum while having strong absorption in the ultraviolet. In addition to polyimide, other polymers having the desired properties are identified below. The processing to form the conductive structure may be performed to form the structure in a commercial roll-to-roll process or similar processing method. Although the desired structure is extremely thin, processing methods have been developed to allow for proper processing.

[0040] The structures described herein avoid using polymers with additives in the polymer to absorb UV light, or avoid using only a single layer to absorb UV light. Therefore, the structures herein are able to maintain a high degree of mechanical stability and stability during the use of the conductive layer. The engineering of the structures described herein provides excellent performance in an extremely thin form that is very suitable for foldable touch screen products. Polymers with suitable optical properties (such as polyimides) can provide a high degree of mechanical strength while providing high flexibility.

[0041] Other transparent double-sided conductive structures have been described in the industry. General patterning of two sides of a transparent substrate with a conductive layer is described in U.S. Patent No. 9,292,141 to Zhong et al. and entitled “Double Sided Touch Sensor on Transparent Substrate” (hereinafter the '141 patent), which is incorporated herein by reference. The '141 patent focuses primarily on transparent conductive films based on conductive oxides such as ITO, but it does refer more broadly to transparent conductive films. Double-sided patterning of a substrate with a nanowire-based conductive layer is described in published U.S. Patent Application No. 2014 / 0202742 to Jones et al. and entitled “Two-Sided Laser Patterning on Thin Film Substrates” (hereinafter the '742 application), which is incorporated herein by reference. The '141 patent and the '742 application do not teach the structures described herein having improved mechanical and optical properties based on materials engineering and achievable through the processing methods described herein.

[0042] For commercial evaluation, various accelerated wear tests have been developed to test the durability of transparent conductive films. The following examples provide tests of double-sided transparent conductive films formed as described herein. Some of the accelerated wear tests are similar, but with slight variations to make the test slightly more or less stringent. The tests are widely used in the industry for testing purposes.

[0043] In order to provide stable processing of thin double-sided conductive structures, the film may be a process that stabilizes the releasable polymer carrier film during the coating step. At the end of processing, the final film may be covered on both surfaces by a polymer release layer, which may protect the film during transportation if further processing is performed at a distance or during storage. In general, the various processing steps may be affected by the processing sequence and processing location. For practical commercial applications, the double-sided conductive film may be processed in one location and transported for patterning and additional processing into a touch sensor, but in principle, the processing may be performed at a single physical location.

[0044] In the case where the polymer substrate is supported by a releasable polymer carrier film, a side of the substrate can be processed to provide a primer layer, a conductive layer with a sparse metal conductive structure, and an outer coating. Dry outer coating can be covered with a polymer release layer, and then the initial releasable polymer carrier layer can be removed to expose the other side of the substrate, wherein the polymer sheet on the first side outer coating is used as a carrier layer for processing the second side. Primer layer, a conductive layer with a sparse metal conductive structure, and an outer coating are applied to the second side of the substrate, usually with respect to the process equipment flip substrate to place the processed side upward. If desired, another releasable polymer sheet can be placed on the dry outer coating of the second processing side to complete the structure for storage and / or transportation. Various other specific embodiments are discussed below.

[0045] The processing improvements and material engineering described herein enable the use of extremely thin substrates while providing and patterning two opposing conductive surfaces. Thus, in some embodiments, the completed structure may have a total thickness of no more than about 35 microns, including the substrate, two conductive layers, the primer layer, and the outer coating. The sheet resistance of each of the opposing layers may not exceed about 100 ohms / square. The resulting double-sided conductive structure may have a total transmittance of at least about 85% of visible light, a haze of no more than about 2.5%, and a b* value of no more than about 4. The properties can be maintained while the overall structure can be extremely flexible, which is further facilitated by the thinness. Therefore, the double-sided conductive structure herein is particularly suitable for forming a transparent touch sensor for flexible electronic devices.

[0046] The basic processing methods involving the use of releasable carrier films to provide processing of very thin structures are outlined in Figure 2, which shows a general processing flow. At the beginning of the illustrated flow, a thin substrate 140 is provided with a first releasable carrier layer 142. Where the first releasable carrier layer 142 covers one surface of the structure, the other surface is processed 144 to form a first transparent conductive coating 146 having a sparse metal conductive layer and any associated layers. After the processing of the first side is completed, a second releasable carrier layer 150 is placed 152 on the conductive coating 146. Where the structure is supported by the second releasable carrier layer 150, the first releasable carrier layer 142 on the other side can be removed 154 to expose the untreated side 156 of the thin substrate 140. For ease of processing, it can optionally be spatially flipped 158 so that the untreated surface faces upward. The other side of the thin substrate 140 is then processed 160 accordingly to form a second transparent conductive coating 162 on the second side of the substrate 140, wherein the second transparent conductive coating 162 typically has a sparse metal conductive layer and any associated layers. To protect second transparent conductive coating 162 prior to patterning or other further processing, a top releasable carrier film 164 can be placed 166 over second transparent conductive coating 162. In some embodiments, the completed structure can be rolled up for shipping and / or storage, if desired.

[0047] The process of forming the transparent conductive layer typically includes deposition of the nanowire ink, drying of the nanowire ink (which may result in fusion to form a fused metal nanostructured network), deposition of an overcoat, and drying and curing of the overcoat. This process may further include deposition of an optional hardcoat as an undercoat between the substrate and the sparse metal conductive layer. As an undercoat, the hardcoat may not provide mechanical protection, but the hardcoat may provide stability to the sparse metal conductive layer, presumably from process damage or other interactions with the substrate. The hardcoat is typically transparent to both visible and near UV light.

[0048] In general, various sparse metal conductive layers can be formed from metal nanowires. Films formed using metal nanowires and treated to planarize the nanowires at junctions to improve conductivity are described in U.S. Pat. No. 8,049,333 to Alden et al., entitled "Transparent Conductors Comprising Metal Nanowires," which is incorporated herein by reference. Structures comprising surface-embedded metal nanowires to increase metal conductivity are described in U.S. Pat. No. 8,748,749 to Srinivas et al., entitled "Patterned Transparent Conductors and Related Manufacturing Methods," which is incorporated herein by reference. However, improved properties have been found for fusing metal nanostructured networks with respect to the desired properties of high conductivity and the desired optical properties of transparency and low haze. Fusion of adjacent metal nanowires can be performed under commercially appropriate processing conditions based on chemical processes.

[0049] Specifically, a significant advance in obtaining conductive films based on metal nanowires is the discovery of a fully controllable process for forming a fused metal network, wherein adjacent portions of metal nanowires are fused into a single structure without different nanowires in the conductive network. Specifically, it was initially discovered that halide ions can drive the fusion of metal nanowires to form fused metal nanostructures. Fluxes containing halide anions were introduced in various ways to successfully achieve fusion with a corresponding significant drop in resistance. It should be noted that halide ions in this process context should not be confused with halide ions used in nanowire synthesis reactions. In particular, fusion of metal nanowires with halide anions has been accomplished using vapors and / or solutions of acyl halides and solutions of halide salts. The fusion of metal nanowires with halide sources is further described in U.S. Pat. No. 10,029,916 to Virkar et al., entitled “Metal Nanowire Networks and Transparent Conductive Material,” and U.S. Pat. No. 9,920,207 to Virkar et al. (the '207 patent), entitled “Metal Nanostructured Networks and Transparent Conductive Material,” both of which are incorporated herein by reference.

[0050] An extension of the process for forming fused metal nanowire networks is based on reduction / oxidation (redox) reactions, which can provide methods for producing fused nanowires without destroying the optical properties of the resulting film. The metal deposited at the junction can be effectively added as a dissolved metal salt, or can be dissolved from the metal nanowires themselves. The effective use of redox chemistry to fuse metal nanowires into nanostructured networks is further described in U.S. Patent No. 10,020,807 to Vilka et al. and entitled "Fused Metal Nanostructured Networks, Fusing Solutions with Reducing Agents and Methods for Forming Metal Networks" (the '807 patent), which is incorporated herein by reference. The '807 patent also describes a single solution method for forming fused metal nanostructured networks. Single solution methods for forming fused metal nanostructured layers are further described in U.S. Pat. No. 9,183,968 B1 to Li et al., entitled “Metal Nanowire Inks for the Formation of Transparent Conductive Films with Fused Networks” (hereinafter the '968 patent), which is incorporated herein by reference, and single solution or ink processes for forming fused metal nanostructured networks are used in the following examples.

[0051] The desired ink to achieve an effective single deposition ink that solidifies into a fused nanostructured metal network contains the desired amount of metal nanowires to achieve an appropriate loading of the metal in the resulting film. The ink is stable in an appropriate solution prior to ink deposition and drying. The ink may contain a reasonable amount of a polymer binder that helps form a stable conductive film for further processing. In order to obtain good fusion results with an ink system, hydrophilic polymers have been found to be effective, such as cellulose or chitosan based polymers. The metal ions as a source of metal for the fusion process may be provided as soluble metal salts.

[0052] A single ink formulation provides for depositing the desired load of metal as a film on the substrate surface and simultaneously provides a component in the ink that induces a fusion process when the ink is dried under appropriate conditions. The ink may be conveniently referred to as a fused metal nanowire ink, with the understanding that fusion typically does not occur until drying. The ink typically comprises an aqueous solvent, which in some embodiments may further comprise an alcohol and / or other organic solvent. The ink may further comprise a dissolved metal salt as a metal source for the fusion process. Without wishing to be limited by theory, it is believed that components of the ink (e.g., an alcohol or other organic composition) reduce metal ions from the solution to drive the fusion process. Previous experience with the fusion process in the system has shown that the metal is preferably deposited at the junction between adjacent metal nanowires. A polymer binder may be provided to stabilize the film and affect the ink properties. The specific formulation of the ink may be adjusted to select ink properties that are suitable for a specific deposition method and have specific coating properties on the substrate surface. As further described below, drying conditions may be selected to effectively perform the fusion process. Two solution fusion systems have also been established and the improved silver nanowires described herein may be utilized.

[0053] The double-sided conductive film can be appropriately patterned to be incorporated into devices such as touch sensors. For patterning, any protective release layer can be removed to expose the outer coating. The outer coating is thin, and patterning generally involves correspondingly patterning the outer coating with a conductive layer. The patterned film can be cut into a desired size. In order to be assembled into a device, an optically transparent adhesive can be applied to the patterned conductive film to attach the film to the device. The transparent conductive structure can be connected to a metal trace along the edge of the film to integrate the transparent conductor into the circuit. Another portion of the optically transparent adhesive can provide a protective cover for the device, which can be a flexible polymer sheet for a desired flexible device. The thin and flexible nature of the double-coated structure described herein provides significant progress for certain device applications.

[0054] Double-sided, individually patternable conductive structures

[0055] The conductive structure of this article includes a conductive layer on the opposite surface, which can provide a separate conductive feature for integration into an electrical device such as a touch sensor. A substrate with good visible light transmittance and good ultraviolet light absorption is selected. A suitable polymer with mechanical properties at a small thickness suitable for a flexible structure is described, which can have high durability. The structure can also have good conductivity stability under accelerated wear test conditions at high temperatures and high humidity values. In some embodiments, the total structure including the protective polymer outer coating may have a total average thickness of no more than about 30 microns, which is required for forming a thinner final product and a flexible display with appropriate mechanical properties. The double-sided conductive structure described herein has achieved the appropriate flexibility of a foldable electronic device assembled into an actual display device to a commercial extent, and based on the test of the application, the double-sided conductive structure with an outer coating on both surfaces can be repeatedly bent around a 1mm diameter mandrel for at least 200,000 times, wherein the sheet resistance of the conductive surface changes by no more than 10%. Experience strongly indicates that the bending can be performed at least several million times.

[0056] The basic structure is shown above Figure 1 In. The polymer substrate is the core of the structure, literally because the conductive layers are applied to both sides, and figuratively in a sense because it provides most of the thickness of the structure. The polymer comprises a polymer as a major component, typically at least more than 50% by weight, which can be referred to as a substrate polymer. Suitable substrate polymers are transparent to visible light. In particular, the transmittance of the substrate polymer is typically at least about 88%, at least about 89% in some embodiments, at least about 90% in other embodiments, and at least about 91% in other embodiments. The optical properties of the overall structure and the measurement of the optical properties are discussed in more detail below, and the relevant general discussion provided in more detail below also applies here. In addition, for a substrate of a selected thickness (the transmittance properties depend on the thickness), the substrate polymer absorbs UV light with a wavelength of 330nm to 370nm so that the transmittance in this wavelength range does not exceed about 15%, does not exceed about 10% in other embodiments, does not exceed about 5% in other embodiments, and does not exceed about 2% in other embodiments. The average thickness of the polymer substrate may typically be no more than about 27 microns, in other embodiments about 1 micron to about 25 microns, and in other embodiments about 5 microns to about 23 microns, but in some embodiments, useful substrates may have a thickness of about 5 microns to about 60 microns. Those skilled in the art will recognize that other ranges of transmittance and thickness within the explicit ranges above are contemplated and are within the present invention.

[0057] Suitable polymers include, for example, polyimides, polysulfides (such as Pylux TM, Ares Materials), polysulfones (e.g., from Solvay), ), or polyethersulfone (e.g. from Solvay or from BASF ) and polyethylene naphthalate (e.g., from DuPont ). Examples based on transparent polyimide are provided below. Conventional aromatic polyimide is colored. But recently developed polyimide is transparent to visible light. Transparent polyimide absorbs extreme ultraviolet light. Transparent polyimide can be obtained from Kolon (Korea), Taimide Tech. (Taiwan, China), Sumitomo (Japan), SKC Corporation (GA, USA) and NeXolve (AL, USA).

[0058] The use of a substrate polymer that absorbs UV light itself avoids the use of a separate layer of UV absorbers or UV fillers in the polymer. Using a separate layer of UV absorbers will increase the thickness of the structure and change the mechanical properties. Using UV absorbers as fillers in polymer substrates can change the mechanical and chemical properties of the polymer substrate. The structures herein rely on the UV absorbing properties of the substrate polymer to achieve highly desired structural properties. The use of polyesters with UV absorbing fillers has been proposed. See published U.S. Patent Application 2014 / 0202742 to Jones et al. and entitled "Double-Sided Laser Patterning on Thin Film Substrates," which is incorporated herein by reference. The use of fillers can change stability and mechanical properties.

[0059] For use in flexible displays, polymer substrates are required to have the required mechanical properties. The durability of the material can be represented in a sense by elongation (which is a measure of the extent to which the material can be stretched without breaking) and / or tensile strength (which is a measure of the force that can be applied before the material fails). Elongation is typically provided by the polymer manufacturer, as measured by a standard procedure, typically ASTM D882. In some embodiments, the elongation is required to be at least about 10%, at least about 15% in other embodiments, and about 20% to about 100% in other embodiments. In some embodiments, the tensile strength of the substrate may be at least about 50 MPa, at least about 60 MPa in other embodiments, and about 65 MPa to about 300 MPa in some embodiments. In addition, for some applications, the elastic (Young's) modulus of the substrate polymer may be about 1.5 GPa to about 7.0 GPa, about 1.75 GPa to about 6.5 GPa in other embodiments, and about 2.0 GPa to about 6 GPa in other embodiments. Those skilled in the art will recognize that other ranges of elongation, tensile strength, and modulus within the explicit ranges above are contemplated and are within the present invention.

[0060] The conductivity on both sides of the structure is provided by a sparse metal conductive layer. The sparse metal conductive layer is discussed in more detail in the following sections. Typically, the thickness of the layer is very small, because the thickness of the nanowire can be on the order of 10-25 nanometers (nm), and slightly thinner nanowires can be obtained in the future. The sparse metal conductive layer can be a fused metal nanostructured network, which is formed by fusing the initially deposited metal nanowires into a single transparent metal structure. After the work of the applicant, academic research laboratories have studied fused metal nanostructured networks. The bending stability of transparent conductive layers on polymer substrates has been evaluated. See Cheng et al., "Highly foldable transparent conductive films composed of silver nanowire junctions prepared by chemical metal reduction", Nanotechnology 25 (2014) 285601 (7 pages) (hereinafter referred to as Cheng et al.). Using less required techniques to fuse silver nanowires, it is still found that fusion provides significant bending stability for the resulting transparent conductive film. In particular, Cheng et al. determined that the fused metal nanostructured network was much more stable in a structure subjected to repeated bending relative to an unfused corresponding structure. It is believed that the use of a fused metal nanostructured network is important for obtaining a structure with long-term stability for use in flexible displays.

[0061] The sparse metal conductive layer is typically covered with a polymeric overcoat to provide mechanical protection to the conductive layer. In some embodiments, the overcoat may be selected so that after application of the overcoat, turbidity is significantly reduced without significantly degrading other properties. In addition, the thickness and composition of the overcoat may be selected so that sheet resistance measurements through the overcoat are not significantly altered relative to measurements without the overcoat. Suitable commercially available coating compositions for the overcoat include, for example, coating solutions from Hybrid Plastics, Inc. (Mississippi, USA). coatings, silica-filled siloxane coatings from California Hardcoating Company (California, USA), Hybrid hard coating materials, SK1100 series hard coating from Dexerials Corporation (Japan), Lioduras from TOYOCHEM (Japan) TM , HC-5619 hardcoat from Addison Clear Wave (IL, USA), CrystalCoat UV curable coating from SDC Technologies, Inc. (CA, USA). Incorporating stabilizers into the overcoat is described in co-pending U.S. patent application Ser. No. 15 / 730,053 to Yang et al., entitled “Stabilized Sparse Metal Conductive Films and Solutions for Delivery of Stabilizing Compounds,” which is incorporated herein by reference.

[0062] There is an overcoat layer on each of the two sparse metal conductive layers, which is generally thin enough to allow conductivity to occur through the overcoat layer, even though the overcoat polymer is generally a dielectric. In other words, the surface with the overcoat layer should generally have about the same sheet resistance as the surface without the overcoat layer. Therefore, it may be desirable for the average thickness of the polymer overcoat layer to be no more than about 250 nm, in some embodiments from about 5 nm to about 200 nm, and in other embodiments from about 10 nm to about 175 nm. Those skilled in the art will recognize that other ranges of thicknesses within the above explicit ranges are contemplated and are within the present invention.

[0063] As described above, the conductive structure may be included in a bottom layer between the polymer substrate and the sparse metal conductive layer. The bottom layer may include a polymer hard coating. As a bottom layer, the polymer hard coating does not provide mechanical protection, but the polymer hard coating can provide protection from chemical attack. As described in the examples, for some polymer substrates, the polymer hard coating bottom layer provides significant stability for the fused metal nanostructured layer, but for some similar thicker substrates, the bottom coating is not used to obtain satisfactory stability. It is not yet understood why some structures are sufficiently stable without the hard coating.

[0064] Suitable hard coat polymers are typically highly crosslinked polymers having crosslinked polyacrylates which may be combined with other crosslinking moieties such as polyurethanes, epoxy polymers, polysiloxanes, and / or other crosslinked polymers. Branched acrylate monomers may form highly crosslinked polymers, and the crosslinked acrylates may be copolymerized with other moieties such as urethane acrylates or the like to form intermeshing crosslinked polymers. Hard coat polymers are commercially available, for example, as coating solutions from Hybrid Composite Plastics, Inc. (Mississippi, USA). coatings, silica-filled siloxane coatings from California Hard Coatings (California, USA), Hybrid hard coating materials, SK1100 series hard coating from Dexerials (Japan), Lioduras from Toyo Chemical (Japan) TM , HC-5619 hardcoat from Addison Clear Wave (Illinois, USA), Crystal Coat UV curable coating from SDC Technologies (California, USA). The hardcoat polymer is further described in published U.S. Patent Application 2016 / 0369104 to Gu et al., entitled “Transparent Polymer Hardcoats and Corresponding Transparent Films,” which is incorporated herein by reference.

[0065] Suitable hardcoat polymers are available that are highly transparent to relevant thicknesses so that the hardcoat does not significantly reduce light transmission through the structure. The polymer hardcoat layers may each independently have an average thickness of about 250 nm to about 4 microns, about 400 nm to about 3.5 microns in other embodiments, and about 500 nm to about 3 microns in other embodiments. Those skilled in the art will recognize that other ranges of hardcoat thicknesses within the above explicit ranges are contemplated and are within the present invention.

[0066] The final structure has a crosslinked outer coating on each surface, which provides a relatively non-sticky surface separately. In order to protect the structure so that it can be transported, stored or the like, one or two surfaces can be protected by a releasable polymer layer. The releasable polymer layer can be formed with a thickness of about 15 microns to about 200 microns, about 20 microns to about 180 microns in other embodiments, about 25 microns to about 170 microns in other embodiments, and about 40 microns to about 150 microns in other embodiments. Those skilled in the art will recognize that other ranges of thickness within the above-mentioned clear and definite range are considered and belong to the present invention. A series of suitable non-sticky polymers can be used for polymer release layers, and because the release layer is removed for further processing, the optical properties are not relevant. Suitable polymers include, for example, polyethylene, polypropylene, polyester, polyamide, polysiloxane, its copolymer and the like. A specific polymer with low viscosity should be selected so that the peel strength of the release layer should be low enough so that the material is not damaged when the release layer is peeled off from the substrate.

[0067] Sparse metal conductive layer

[0068] Sparse metal conductive layers are typically formed from metal nanowires. With sufficient loading and selection of nanowire properties, reasonable conductivity can be obtained using nanowires with corresponding appropriate optical properties. It is expected that transparent conductive film structures formed with silver nanowires can produce the desired properties of double-sided conductive films with structures with various sparse metal conductive structures described herein. However, fused metal nanostructured networks have been used to obtain particularly desirable properties. The discussion herein focuses on embodiments involving fused metal nanostructured networks, which have been found to provide improved performance properties as transparent conductive films.

[0069] Several practical methods have been developed to accomplish metal nanowire fusing. Metal loading can be balanced to obtain a desired degree of conductivity and good optical properties. In general, metal nanowire processing can be accomplished by depositing two inks, wherein the first ink comprises metal nanowires and the second ink comprises a fusing composition, or by depositing an ink that combines fusing elements into a metal nanowire dispersion. The ink may or may not further comprise additional processing acids, binders, or the like. A suitable patterning method may be selected to suit a particular ink system.

[0070] In general, one or more solutions or inks for forming metal nanostructured networks may collectively contain well-dispersed metal nanowires, fluxing agents, and optional additional components, such as polymer binders, crosslinking agents, wetting agents, such as surfactants, thickeners, dispersants, other optional additives, or combinations thereof. The solvent used for the metal nanowire ink and / or the fusion solution may contain an aqueous solvent, an organic solvent, or a mixture thereof if it is different from the nanowire ink. Specifically, suitable solvents include, for example, water, alcohols, ketones, esters, ethers (such as glycol ethers), aromatic compounds, alkanes, and the like and mixtures thereof. Specific solvents include, for example, water, ethanol, isopropanol, isobutanol, tert-butanol, methyl ethyl ketone, glycol ethers, methyl isobutyl ketone, toluene, hexane, ethyl acetate, butyl acetate, ethyl lactate, PGMEA (2-methoxy-1-methylethyl acetate), dimethyl carbonate, or mixtures thereof. Although the solvent should be selected based on the ability to form a good dispersion of metal nanowires, the solvent should also be compatible with other selected additives so that the additives are soluble in the solvent. For embodiments where a flux is included in a single solution with metal nanowires, the solvent or a component thereof may or may not be an important component of the fusing solution (eg, an alcohol) and may be selected accordingly if desired.

[0071] The metal nanowire ink in one ink or two ink configurations may include about 0.01 wt % to about 1 wt % metal nanowires, in other embodiments about 0.02 wt % to about 0.75 wt % metal nanowires, and in additional embodiments about 0.04 wt % to about 0.5 wt % metal nanowires. One skilled in the art will recognize that other concentration ranges of metal nanowires within the explicit ranges above are contemplated and are within the present invention. The concentration of the metal nanowires affects the loading of the metal on the substrate surface as well as the physical properties of the ink.

[0072] Silver provides excellent electrical conductivity. TM Inks Suitable silver nanowire inks are sold for forming fused metal nanostructured networks. Other sources of silver nanowires are commercially available, and the basic fusion techniques are fully described in the aforementioned '207 and '807 patents.

[0073] The polymer binder and solvent are generally always selected so that the polymer binder is soluble or dispersible in the solvent. In suitable embodiments, the metal nanowire ink generally comprises about 0.02 wt % to about 5 wt % binder, in other embodiments about 0.05 wt % to about 4 wt % binder and in additional embodiments about 0.1 wt % to about 2.5 wt % polymer binder. In some embodiments, the polymer binder comprises a crosslinkable organic polymer, such as a radiation crosslinkable organic polymer and / or a thermally curable organic binder. To facilitate crosslinking of the binder, in some embodiments, the metal nanowire ink may comprise about 0.0005 wt % to about 1 wt % crosslinking agent, in other embodiments about 0.002 wt % to about 0.5 wt % and in additional embodiments about 0.005 wt % to about 0.25 wt %. The nanowire ink may optionally comprise a rheology modifier or a combination thereof. In some embodiments, the ink may comprise a wetting agent or surfactant to reduce surface tension, and the wetting agent may be used to improve coating properties. The wetting agent is generally soluble in the solvent. In some embodiments, the nanowire ink may include about 0.001 wt % to about 1 wt % wetting agent, in other embodiments about 0.002 wt % to about 0.75 wt % and in other embodiments about 0.003 wt % to about 0.6 wt % wetting agent. A thickener may optionally be used as a rheology modifier to stabilize the dispersion and reduce or eliminate sedimentation. In some embodiments, the nanowire ink may optionally include about 0.05 wt % to about 5 wt % thickener, in other embodiments about 0.075 wt % to about 4 wt % and in other embodiments about 0.1 wt % to about 3 wt % thickener. One skilled in the art will recognize that other concentration ranges of binder, wetting agent, and thickener within the above explicit ranges are contemplated and are within the present invention.

[0074] A variety of polymer binders may be suitable for dissolving / dispersing in solvents for metal nanowires, and suitable binders include polymers developed for coating applications. Hard coating polymers (e.g., radiation curable coatings) are commercially available, for example, as hard coating materials for a variety of applications, which may be selected for dissolution in aqueous or non-aqueous solvents. Suitable classes of radiation curable polymers and / or thermally curable polymers include, for example, polyurethanes, acrylic resins, acrylic copolymers, cellulose ethers and esters, other water-insoluble structural polysaccharides, polyethers, polyesters, epoxy-containing polymers, and mixtures thereof. Examples of commercial polymer binders include, for example, Trademark acrylic resin (DMS new resin (DMSNeoResins)), Trademark acrylic copolymers (BASF Resins), Trademark acrylic resin (Lucite International), Trademark urethanes (Lubrizol Advanced Materials), cellulose acetate butyrate polymers (CAB trademark, from Eastman TM Chemistry (Eastman TM Chemical))、BAYHYDROL TM Trademark polyurethane dispersion (Bayer Material Science), Trademark polyurethane dispersion (Cytec Industries, Inc.), Trademark polyvinyl butyral (Kuraray America, Inc.), cellulose ethers (e.g., ethyl cellulose or hydroxypropyl methyl cellulose), other polysaccharide-based polymers (e.g., chitosan and pectin), synthetic polymers (e.g., polyvinyl acetate), and the like. In particular, it has been found that polysaccharide-based polymers are desirable as binders in sparse metal conductive layers. The polymer binder may crosslink itself upon exposure to radiation, and / or it may crosslink with a photoinitiator or other crosslinking agent. In some embodiments, the photocrosslinker may form free radicals upon exposure to radiation, and the free radicals subsequently induce a crosslinking reaction based on a free radical polymerization mechanism. Suitable photoinitiators include, for example, commercially available products, such as Trademark (BASF), GENOCURE TM Trademark (Rahn USA Corp.) and Trademark (Double Bond Chemical Ind., Co., Ltd.), combinations thereof, or the like.

[0075] Wetting agents can be used to improve the coatability of metal nanowire inks and the quality of metal nanowire dispersions. Specifically, wetting agents can reduce the surface energy of the ink so that the ink is fully diffused onto the surface after coating. The wetting agent can be a surfactant and / or a dispersant. Surfactants are a class of materials used to reduce surface energy, and surfactants can improve the solubility of materials. Surfactants generally have a hydrophilic portion of the molecule and a hydrophobic portion of the molecule, which promotes its properties. A wide range of surfactants (e.g., nonionic surfactants, cationic surfactants, anionic surfactants, zwitterionic surfactants) are commercially available. In some embodiments, if the properties associated with the surfactant are not a problem, non-surfactant wetting agents (e.g., dispersants) are also known in the industry and can effectively improve the wetting ability of the ink. Suitable commercial wetting agents include, for example, COATOSIL TMTrademark Epoxy-functionalized silane oligomers (Momentum Performance Materials), SILWET TM Trademark organic polysilicone surfactant (Momentum Performance Materials), THETAWET TM Trademark short-chain nonionic fluorinated surfactants (ICT Industries, Inc.), Trademark polymer dispersants (Air Products Inc.), Trademark polymer dispersant (Lubrizol), Fluorinated surfactants (DuPont TM )、XOANONS WE-D545 surfactant (Anhui Xoanons Chemical Co., Ltd.), EFKA TM PU 4009 polymer dispersant (BASF), MASURF FP-815CP, MASURF FS-910 (Mason Chemicals), NOVEC TM FC-4430 fluorinated surfactant (3M), mixtures thereof, and the like.

[0076] Thickeners can be used to improve the stability of the dispersion by reducing or eliminating solids settling from the metal nanowire ink. Thickeners may or may not significantly change the viscosity or other fluid properties of the ink. Suitable thickeners are commercially available and include, for example, CRAYVALLAC TM Modified urea of ​​the trademark, such as LA-100 (Cray Valley Acrylics, USA), polyacrylamide, THIXOL TM 53L trademark acrylic thickener, COAPUR TM 2025, COAPUR TM 830W, COAPUR TM 6050、COAPUR TM XS71 (Coatex, Inc.), Modified urea of ​​the trademark (BYK Additives), Acrysol DR 73, Acrysol RM-995, Acrysol RM-8W (Dow Coating Materials), Aquaflow NHS-300, Aquaflow XLS-530 hydrophobically modified polyether thickener (Ashland Inc.), Borchi Gel L75N, Borchi Gel PW25 (OMG Borchers), and the like.

[0077] Additional additives may be added to the metal nanowire ink, each in an amount typically not exceeding about 5 wt %, in other embodiments not exceeding about 2 wt %, and in other embodiments not exceeding about 1 wt %. Other additives may include, for example, antioxidants, UV stabilizers, defoamers or anti-foaming agents, anti-settling agents, viscosity modifiers, or the like.

[0078] The following describes a process for forming a fused metal nanostructured layer.

[0079] Optical and electrical properties of the double-sided structure

[0080] Transparent structures with double-sided conductive films incorporating sparse metal conductive layers (e.g., fused metal nanostructured networks) can provide low resistance while providing good optical properties. Thus, the films can be used as transparent conductive electrodes or the like. Transparent conductive electrodes can be suitable for a range of applications. For displays and in particular for touch screens, the films can be patterned independently on each side to provide a conductive pattern formed by the film. Double-sided conductive structures generally have good optical properties with respect to high transmittance, low haze, and low color.

[0081] The resistance of the film can be expressed as a sheet resistance, which is reported in units of ohms per square (Ω / □ or ohms / square) to distinguish the value from the overall resistance value according to parameters related to the measurement process. The sheet resistance of the film is typically measured using a four-point probe measurement or another suitable process. In some embodiments, the sheet resistance of the conductive surface of the structure may not exceed about 200 ohms / square, in other embodiments not more than about 150 ohms / square, in additional embodiments not more than about 100 ohms / square and in other embodiments not more than about 75 ohms / square. Those skilled in the art will recognize that other ranges of sheet resistance within the above-specified ranges are considered and belong to the present invention. In an example, a transparent conductive film with a target sheet resistance of 50 ohms / square is formed. In general, the sheet resistance can be reduced by increasing the loading of the nanowires, but from other perspectives, the increased loading may or may not be desired.

[0082] For applications as transparent conductive films, it is necessary to maintain good optical transparency in the fused metal nanowire network or other sparse metal conductive layer. In principle, optical transparency is inversely related to loading, where higher loading leads to reduced transparency, but processing of the network can also significantly affect transparency. Similarly, polymer binders and other additives can be selected to maintain good optical transparency. Transparency can be reported as a dimensionless quantity, transmittance. Transmittance is the ratio of the transmitted optical density (I) to the incident optical density (I o ). The transmittance of a transparent conductive layer within a double-sided conductive structure with an outer coating is reported in the following examples. The optical transmittance of a transparent conductive layer can be evaluated relative to the transmitted light through the substrate supporting the transparent conductive film. For example, the transparency of the conductive film described herein can be measured by using a UV-visible spectrophotometer and measuring the total transmittance through the conductive film and the supporting substrate. The transmittance value of the transparent conductive layer on the transparent film substrate is reported. If necessary, the transmittance through the individual layers can be estimated by measuring various intermediates based on the approximation of the total transmittance as the product of the individual transmittances.

[0083] Although good optical transparency in the visible spectrum is generally desired, for convenience, optical transmittance may be reported at a wavelength of 550 nm for light. Alternatively or additionally, transmittance may be reported as total transmittance for wavelengths of 400 nm to 700 nm for light, and the results are reported in the following examples. In general, for fused metal nanowire films, measurements of 550 nm transmittance and total transmittance from 400 nm to 700 nm (or just "total transmittance" for convenience) are not qualitatively different. In some embodiments, the total transmittance (TT %) of the double-sided conductive structure is at least 85%, in other embodiments at least about 88%, in other embodiments at least about 89%, in other embodiments from about 90% to about 96%, and in some embodiments from about 90.5% to about 95%. The transmittance of the film can be evaluated using the standard ASTM D1003 ("Standard Test Method for Haze and Luminous Transmittance of Transparent Plastics"), which is incorporated herein by reference. One skilled in the art will recognize that other ranges of transmittance within the explicit ranges above are contemplated and are within the present invention.

[0084] The fused metal network can also have low turbidity and high visible light transmittance while having the desired low sheet resistance. The turbidity can be measured using a turbidity meter based on the ASTM D1003 mentioned above, and the turbidity contribution of the substrate can be removed to provide a turbidity value for the transparent conductive film. The turbidity measured based on ASTM D1003 is a turbidity based on transmittance, and a separate measurement can be made for the turbidity based on reflection. Unless otherwise explicitly stated, turbidity refers to turbidity based on transmittance. In some embodiments, the turbidity value of the transparent conductive film may not exceed about 2.5%, in other embodiments not exceed about 2.25%, in additional embodiments not exceed about 2.0% and in other embodiments, about 0.6% to about 1.75%. It has been found that the selected transparent outer coating can significantly reduce the turbidity of the structure with the transparent conductive layer, and the value of the structure with the outer coating can be considered relative to the range of turbidity values. The polymer outer coating is discussed above. It should be recognized by those skilled in the art that other ranges of turbidity within the above-mentioned clear range are considered and belong to the present invention.

[0085] The double-sided conductive structure may also be required to be substantially white, i.e., have little color. A color space may be defined as relating spectral wavelengths to human perception of color. CIELAB is a color space determined by the International Commission on Illumination (CIE). The CIELAB color space uses a three-dimensional coordinate system L*, a*, and b*, where L* relates to the brightness of a color, a* relates to the position of a color between red and green, and b* relates to the position of a color between yellow and blue. The "*" value represents a normalized value relative to a standard white point. The CIELAB parameters may be determined using commercial software from measurements made in a spectrophotometer.

[0086] Based on CIELAB parameters, in principle, a double-sided conductive structure with an appropriate polymer substrate can be designed to obtain reasonable whiteness, usually based on small absolute values ​​of b* and a* in the CIELAB scale. In some embodiments, in view of practical limitations, the design of the film can guide the result to produce whiter light (absolute values ​​of b* and a* below the target cutoff value) in certain desired ranges, as has been achieved with nanoscale colorants. As further explained below, reasonable whiteness values ​​can be obtained, and the total transmittance of visible light can be acceptably reduced. In some embodiments, the b* value of the double-sided conductive structure may not exceed about 4.0, in other embodiments not exceed about 3.75, and in other embodiments not exceed about 3.5, but lower values ​​are still possible with the appropriate selection of substrates that contribute most of the b* value.

[0087] The nanoscale colorant may be, for example, a nanoscale metal structure or a nanoscale pigment. The nanoscale metal structure typically has at least one average dimension of no more than about 100 nm. For example, the average thickness of the nanoplate is no more than 100 nm, the thickness of the nanobelt may be no more than about 100 nm, and the width may be no more than 100 nm. Metal nanoplates can be synthesized using solution-based techniques, and their optical properties have been examined. Silver nanoplates with tuned absorption properties based on surface plasmon resonance can be purchased from nanoComposix, Inc., San Diego, CA, USA, Beijing Nanomeet Technology Co. Ltd., China, and Suzhou ColdStones Technology Co., Ltd., China. Larger scale synthesis of silver nanoplates is described in U.S. Pat. No. 10,147,512 to Hu et al., entitled “Methods for Synthesizing Silver Nanoplates and Noble Metal Coated Silver Nanoplates and Their Use in Transparent Films for Hue Control,” which is incorporated herein by reference.

[0088] deal with

[0089] Processing methods have been developed to allow for reproducible formation of double-sided conductive structures having the thin dimensions described herein. In some embodiments, structures are sequentially formed on one side at a time. While one side is being processed, the other side of the structure is typically supported on a release layer (e.g., the polymer release layer described above). Processing can generally be conceptualized, albeit somewhat arbitrarily, as conveniently broken down into five parts: 1) preparing the substrate for processing, 2) processing the first side, 3) preparing the structure for processing the second side, 4) processing the second side, and 5) completing the structure for shipping and / or storage.

[0090] In preparing the structure for coating, a substrate is obtained and provided on a release layer on one side with the opposite surface exposed for coating. The substrate sheet is usually symmetrical so that either surface can be selected as the first surface for processing. The release layer used to support the substrate for processing should be selected to have a thermal stability suitable for processing, which generally means that the melting point should be greater than about 180°C. For some polymer substrate materials, the glass transition temperature (T g) can also be significant. In some embodiments, T g is at least about 100°C, and in other embodiments T g It may be at least about 120°C. If the substrate supplier supplies the substrate without a release layer or on a release layer that does not have the required thermal stability, the substrate is placed on a suitable thermally stable release layer and, if appropriate, the initially supplied release layer is removed to expose the first surface for coating. The substrate film on the thermally stable release layer is then prepared for processing. Suitable release layer sheets are described above.

[0091] For embodiments with hard coating, a primer layer may be formed on the exposed surface next. In some embodiments with hard coating, a substrate supplier may provide a substrate already having a hard coating, so that from a process perspective, it may be assumed that the hard coating is only a portion of the substrate. For the deposition of a hard coating precursor solution, any reasonable deposition method may be used, such as dip coating, spray coating, blade coating, rod coating, Meyer-rod coating, slot die coating, gravure printing, spin coating or the like. The deposition method directs the amount of the deposited liquid, and the concentration of the solution may be adjusted to provide a product coating of a desired thickness on the surface. After forming the coating with a dispersion, the coating may be dried to remove the liquid and appropriately cross-linked. Drying may be performed in any reasonable manner, such as exposure to the environment, heating in an oven, blowing hot air over the coated structure, using a heating lamp, a combination thereof or the like. Typically, the hard coating is cross-linked with UV light or with heat, and a cross-linking initiator may or may not be used.

[0092] Whether or not a hard coat is applied, a sparse metal conductive layer is subsequently applied. In some embodiments, a process for initially depositing a sparse nanowire film is used, and further processing may or may not involve fusion of silver nanowires. As described above, fusion into a single fused metal nanostructured network can provide improved properties of a transparent conductive film. For the deposition of the metal nanowire ink, any reasonable deposition method can be used, such as dip coating, spray coating, knife edge coating, rod coating, Mel rod coating, slot die coating, gravure printing, spin coating, or the like. The ink may have properties, such as viscosity, that are appropriately adjusted using additives for the desired deposition method. Similarly, the deposition method guides the amount of liquid deposited, and the concentration of the ink can be adjusted to provide a desired load of metal nanowires on the surface. After forming a coating with the dispersion, the sparse metal conductive layer can be dried to remove the liquid.

[0093] The fusion of metal nanowires can be accomplished via various reagents. Without wishing to be bound by theory, it is believed that fluxing agents can mobilize metal ions, and free energy appears to decrease during the fusion process. In some embodiments, excess metal migration or growth can result in reduced optical properties, and therefore, the desired results can be obtained in a reasonably controlled manner via equilibrium shifts, usually for a short period of time, to form enough fusion to obtain the desired conductivity while maintaining the desired optical properties. In general, the fusion process can be performed using controlled exposure to fusion vapors and / or via the use of fluxing agents in a solution. Under appropriate conditions, the fused metal conductive network is a single structure.

[0094] In some embodiments, the initiation of the fusing process can be controlled by partially drying the solution to increase the concentration of the component, and the quenching of the fusing process can be accomplished by, for example, rinsing or more completely drying the metal layer. In some embodiments, a subsequent process of depositing another ink fuses the metal nanowires into the conductive fused metal nanostructured network. A flux can be incorporated into a single ink along with the metal nanowires. An ink formulation for forming a single fused metal conductive network having thin and uniform metal nanowires is described in the following examples.

[0095] The metal nanowire layer may be dried using, for example, a heat gun, oven, heat lamp, or the like, but in some embodiments, an air-dryable film may be desired. In some embodiments, the film may be heated to a temperature of about 50° C. to about 150° C. during drying. Drying conditions may be designed to control the fusing process, but ink design may appropriately use process conditions that are readily available in conventional process equipment. After drying, the film may be washed one or more times with, for example, alcohol or other solvents or solvent blends such as ethanol or isopropanol to remove excess solids to reduce turbidity.

[0096] As described above, one or more overcoats may be applied over the sparse metal conductive layer. The overcoat treatment is similar to the undercoat treatment described above, with appropriate substitutions of the coating solution. Patterning and other further treatments after the overcoat is applied are further described below.

[0097] After applying the overcoat and drying / curing the overcoat on the first processing side, the overcoat may be covered by a release layer. The second side may remove the release layer to expose the second surface of the substrate for processing of the transparent conductive layer. Removing the release layer from the second surface and placing the release layer on the first surface may be performed sequentially or approximately simultaneously. The sequential removal and placement of the release layer may generally be performed in any order, but it may be desirable to first place the release layer on the processed first layer to avoid moving the unsupported substrate through the conveyor system for a considerable distance. In addition, placing the release layer sequentially on the first processing side of the substrate will be consistent with subsequently flipping the structure so that the release layer is removed from the second surface while the second surface is facing upward, which maintains all processing associated with the facing upward surface. The simultaneous or approximately simultaneous execution of the tasks may be understood by the eyes of a person skilled in the art as components that are close enough to accompany the tasks so that their designs influence each other.

[0098] Once the second surface is exposed by removing the release layer, the second surface can be treated similarly to the first surface. In particular, if a hard coating (priming layer) is required and is not supplied with the substrate, the hard coating can be applied as described above. The deposition and treatment of the sparse metal conductive layer (usually a fused metal nanostructured network) can be deposited as described above. After applying and drying and / or curing the sparse metal conductive layer, the outer coating can then be applied and dried / cured as described above. After completing the treatment of the transparent conductive layer on the second side of the substrate, a release layer can be used to cover this surface.

[0099] In some embodiments, the process is efficiently performed on a roll-to-roll format, where a roll of substrate is patterned and the processed structure is rolled up for further processing. The roll-to-roll process will be suitable for commercial coating equipment and conveyors. To process the second side, the rolled product of the first side coating can be flipped to unfold the rolled structure so that the other surface faces the coating head.

[0100] A schematic diagram of roll-to-roll processing of one surface of a substrate is shown in Figure 4. A substrate supply roll 200 provides a substrate sheet 202, which is carried by a conveyor system 204. If the substrate supply roll 200 provides a substrate having an initial release layer 206 on a first surface 208 and wherein the initial release layer 206 is removed prior to further processing, the initial release layer 206 may be separated from the substrate sheet 202 and placed in an initial release layer take-up roll 210. If a process release layer 212 is placed on a second surface of the substrate sheet 202 to support the substrate during processing, the process release layer 212 may be dispersed from a process release layer roll 214. Lamination rolls 216, 218 may be used to laminate the process release layer 212 with the substrate sheet 202, which may or may not involve heat and reasonable pressure. If the substrate is provided on the substrate supply roll 200 without an initial release layer, there will be no process of peeling and rolling up the initial release layer. Furthermore, if the substrate is provided on the substrate supply roll 200 already having the process release layer, the structure of providing the process release layer from the roll and the lamination of the process release layer with the substrate are not required.

[0101] Utilizing the substrate sheet 202 prepared with the process release layer 212, the coating can be applied to the first surface 208 of the substrate sheet 202. If a hard coating bottom layer is to be applied, a hard coating precursor solution can be applied with a first coating machine 230 (e.g., a slot coating machine that applies a selected thin coating from a reservoir). Utilizing the applied hard coating precursor solution, the substrate sheet 202 can go to a first coating processor station 232. The first coating processor station 232 can include a drying tool and / or a radiation source. The drying tool can supply heat to remove solvents and / or cross-linked polymers, and suitable drying tools include, for example, ovens, hot air blowers, heat lamps, and the like. Suitable radiation sources include, for example, UV lamps, electron beams, or other suitable radiation sources. Heat lamps can supply required heat and radiation, such as infrared radiation, in principle. For UV curable hard coatings, the radiation source can be a UV light source.

[0102] Whether or not a hardcoat primer is applied, the nanowire ink is applied to the substrate sheet 202 using a second coater 240 to form a sparse metallic conductive layer. After the nanowire ink is applied, the substrate sheet 202 proceeds to a second coating processor station 242. The second coating processor station 242 may include a drying tool and / or a radiation source. Suitable drying tools and radiation sources are as described above for the first coating processor station 232, and are equally applicable to the second coating processor station 242, as written herein. If the nanowire ink comprises a fused solution, the resulting sparse metallic conductive layer may comprise a fused metallic nanostructured network.

[0103] After forming the sparse metal conductive layer, the substrate sheet 202 goes through the conveyor system 204 to apply the outer coating. In particular, the third coater 250 is used to apply the outer coating precursor solution on the sparse metal conductive layer. Then, the conveyor system 204 transports the substrate sheet 202 with the outer coating precursor solution to the third coating processor station 252. The third coating processor station 252 may include a drying tool and / or a radiation source. Suitable drying tools and radiation sources are described above for the first coating processing station 232, and are also applicable to the third coating processor station 252, as written here. In an actual commercial roll-to-roll processor, the first coating processor station 232 (if present), the second coating processor station 242 and the third coating processor station 252 may be the same or different from each other relative to any pair of the three, even if the possible design range of the three processing stations is substantially the same.

[0104] After the outer coating is completed, if no additional processing of the first surface 208 is required before processing the second surface on the other side of the substrate sheet 202, then the second process release layer 260 can be delivered from the supply roll 262 and placed on the outer coating on the substrate sheet 202. The substrate 202 and the second process release layer 260 can be laminated with rollers 264, 266. With the second process release layer 260 in place, the substrate sheet 202 can be placed on a storage roll 268. If necessary, the first process release layer 212 can be removed before placing the process substrate sheet 202 on the storage roll 268, but this release of the first process release layer can be performed at the beginning of the processing of the second surface. In another alternative embodiment, the substrate sheet 202 can be placed on the storage roll 268 without placing the second process release layer, so that the supply roll 262 and the rollers 264, 266 will not be required. Then, at the beginning of processing the second surface, the second process release layer 260 can be placed on the substrate sheet 202.

[0105] Although in principle the second layer can be processed without the substrate sheet 202 being placed on the storage roller 268, there are practical obstacles, but this is still an option. Usually, due to gravity, it is not necessary to apply the coating on the lower surface. The substrate sheet that flips and moves will usually require a large amount of space or lateral stacking of process equipment. Although the obstacles described are not insurmountable, it is usually more convenient to place the substrate sheet 202 on the storage roller 268 and move the roller to the position of the second side of the process. For example, the storage roller 268 can be turned over and placed in the position of the supply roller 200, and then the substrate sheet comes from the top of the roller instead of the bottom. Appropriate treatment can be performed to expose the second surface so that it can be processed under the support of the second process release layer 260, which can be placed in a suitable position when the first surface is finished or when the second surface is started. Then, the same or equivalent process components can be used to process the second surface of the substrate sheet 202 similarly to the first surface. At the end of processing the second surface of the substrate layer 202, the second surface may or may not be covered with a release layer, and the substrate sheet may or may not have been previously placed on a storage roll. In any case, the double-coated substrate sheet can then be ready for further processing into a device at the same location or at a remote location after transportation.

[0106] Touch sensor and corresponding processing

[0107] Although the double-sided transparent conductive structure can be used for various applications, the structure is particularly useful for forming a touch sensor. Patterning can be performed on each side of the structure to form the conductive pattern required for a touch sensor or the like. In general, patterning can be performed using various patterning techniques in the industry. One commercial patterning method for touch sensors is based on UV laser ablation. The UV laser light will have a wavelength absorbed by the substrate, and suitable UV lasers typically operate at 190nm to 355nm. Alternatively, photolithography can be used for patterning, in which a photosensitive composition (i.e., a photoresist) is patterned with patterned irradiation, for example, via a mask, or with direct write lithography equipment. The latent image in the photoresist is developed to form a physical pattern, which is then transferred to the conductive layer.

[0108] Once the conductive layer is patterned, additional layers can be placed over the patterned conductive layer to incorporate the structure into a device. Flexible light-conductive adhesives can be used to secure the patterned double-sided conductive structure to other structures along both surfaces. Suitable adhesive tapes are commercially available, for example, from Lintec Corporation (MO series); Saint Gobain Performance Plastics (DF713 series); Nitto Americas (Nitto Denko) (LUCIACS CS9621T and LUCIACS CS9622T); LG Hausys OCA (OC9102D, OC9052D); DIC Corporation (DAITAC LT series OCA, DAITAC WS series OCA, and DAITAC ZB series); PANAC Plastic Film Company (PANACLEAN series); Tesa SE (Germany) (AF61, 694 series, 696 series, and 697 series); Minnesota Mining and Manufacturing Company (Minnesota Mining and Manufacturing Company). Manufacturing) (3M, Minnesota, USA - Product Nos. 8146, 8171, 8172, 8173, 1414-1, 9894 and similar products) and Adhesive Research (e.g., product 8932). Typically, metal traces can be connected to the transparent conductive layer along the edge of the pattern to provide the final connection to the circuit.

[0109] With respect to the corresponding properties of multilayer films, the additional components are generally selected to have a small effect on the optical properties, and a variety of coatings and substrates are commercially available for use in transparent elements. Suitable optical coatings, substrates, and related materials are summarized above. Some structural materials may be electrically insulating, and if thicker insulating layers are used, the films may be patterned to provide access and electrical contacts to other embedded conductive elements.

[0110] To produce a sensor or the like, patterning is typically performed as outlined above to produce conductive areas and electrically insulating areas, both of which are transparent. A schematic diagram of the layout of a portion of a touch sensor viewed from above is shown in Figure 3 Wires D0-D4 will be along one transparent conductive surface and wires S0-S4 will be on the other transparent conductive surface of the structure. In some embodiments, if a touch is near the intersection of lines Dn and Sm, an electrical signal can be directed along conductive line Dn so that sensing is performed along conductive line Sm. The capacitive response of the wire is changed by the touch.

[0111] Transparent Conductive Film Stability and Stability Test

[0112] In use, transparent conductive films need to last for a commercially acceptable time, such as the life of the corresponding device. The stable compositions and structures described herein are intended to have this goal and are sufficient to maintain the properties of sparse metal conductive layers. To test performance, accelerated aging procedures can be used to provide objective evaluations within a reasonable period of time. The tests can be performed using commercially available environmental test equipment.

[0113] The selected test (Xenon Test) used in the Examples involved a black standard temperature of 60°C (setting for the apparatus), an air temperature of 38°C, a relative humidity of 50% and a power of 60 W / m from a Xenon lamp with a daylight filter. 2 (300nm to 400nm) irradiance. Various suitable test equipment are commercially available, such as the Atlas Suntest TM XXL equipment (Atlas Material Testing Solutions, Chicago, IL, USA) and SUGA environmental testing instruments, super xenon weatherometer, SX75 (SUGA Test Instruments Co., Limited, Japan). In the second accelerated wear test, the chamber temperature was set at 85°C and the relative humidity was set at 85% without illumination. For this high temperature and high humidity test, suitable equipment is commercially available, such as ESPEC model BTL-433 environmental chamber (ESPEC North America, Inc., Hudsonville, MI, USA) and Thermotron SM-3.5-3800 benchtop environmental chamber (Thermotron Inc., Holland, MI, USA). The following examples provide tests using two different stacking structures incorporating fused metal nanostructured networks, and the specific stacking structures are described below.

[0114] Under the test conditions specified in the previous paragraph, the specimen can be evaluated by the change in sheet resistance over time. The values ​​can be normalized to the initial sheet resistance to focus on the time evolution. Therefore, in general, for R t / R0 plots the time evolution, where R t is the time-evolved sheet resistance measurement result and R0 is the initial value of the sheet resistance. In some embodiments, after 1000 hours of environmental testing, R tThe value of / R0 may not exceed a value of 1.8, in other embodiments not exceed a value of 1.6, in other embodiments not exceed a value of 1.4, and after 500 hours of environmental testing, in other embodiments not exceed a value of 1.2. From another perspective, after about 1000 hours of environmental testing, R t The value of / R0 may not exceed a value of 1.5, in other embodiments not exceed a value of 1.5 after about 1500 hours of environmental testing, and in other embodiments not exceed a value of 1.5 after about 2000 hours of environmental testing. In additional embodiments, after about 750 hours, R t The value of / R0 may not exceed a value of 1.2. Those skilled in the art will recognize that considering R within the above explicit range t / R0 and other ranges of stabilization time are possible and belong to the present invention.

[0115] Examples

[0116] The optical properties of the transparent conductive films were examined for silver nanowires formed into films within the double coating structure described herein. Activegrid from C3Nano Inc. TM The ink forms a film. Processing details and structures are further described below.

[0117] The measurements were performed on the specific structures shown below. For the conductive structures, a transparent conductive film was formed using silver nanowire ink substantially as described in Example 5 of the '968 patent cited above. TM The product has silver nanowires with an average diameter of about ~20-25 nm. The drying process in the roll-to-roll process described below induces chemical fusion because the solvent is removed to concentrate the components, where further reactions are terminated by continued drying. The amount of silver deposited is selected so that the sheet resistance of the film is about 50 ohms / square or 70 ohms / square, as described in the specific samples below. After drying the conductive film, a commercial overcoat is slit coated on the dried transparent conductive film in a roll-to-roll process. The overcoat is dried and cross-linked with a UV lamp to form an overcoat with a thickness of about 50-100 nm.

[0118] Optical and electrical properties testing

[0119] Sheet resistance, total transmittance (TT), haze, and b* values ​​were obtained for a series of examples. Sheet resistance (Ω / □) was measured using a 4-point probe method (a non-contact resistance meter) or by measuring the resistance of the film using a square defined by two solid (non-transparent) silver lines formed of silver paste. In some embodiments, a pair of parallel silver paste strips were applied to the sample surface to define a square or rectangular shape, which was then annealed at about 120° C. for 20 minutes to cure and dry the silver paste. Alligator clips were connected to the silver paste strips, and the leads were connected to a commercial resistance measurement device.

[0120] The total transmittance (TT) and turbidity of the film samples were measured using a turbidimeter. The instrument is designed to evaluate optical properties based on the ASTM D1003 standard ("Standard Test Method for Turbidity and Luminous Transmittance of Transparent Plastics"), which is incorporated herein by reference. The total transmittance and (transmittance) turbidity of the film include the substrate. The polyimide substrate used in Examples 1-4 and 6 had a total transmittance of 91.5%, a turbidity in the range of 0.12% to 0.17%, and a b* in the range of 0.74 to 0.80. The substrate of Example 5 has similar optical properties. The optical properties were evaluated using commercial software by using a SpectraMagic TM The CIELAB value of b* was determined by measurements performed with a Konica Minolta spectrophotometer CM-3700A using NX software.

[0121] Reliability Test

[0122] Since transparent conductive films need to last for a commercially acceptable time, such as the life of the corresponding device, various accelerated aging tests are used to provide objective evaluation within a reasonable period of time. Specific tests are 65°C / 90% RH (relative humidity), 85°C / 85% RH and xenon lamp tests, which are described in further detail below. The tests are performed using commercially available environmental test equipment described below.

[0123] Both tests were performed at 85°C and 85% relative humidity or 65°C / 90% RH without irradiation. The tests are referred to as 85°C / 85% RH test or 65°C / 90% RH test, respectively.

[0124] Another test involved a black standard temperature of 60°C (setting for the device), an air temperature of 38°C, a relative humidity of 50% and 60 W / m from a xenon lamp with a daylight filter. 2 (300nm to 400nm) irradiance. This test is called the xenon lamp test. Various suitable test equipment is commercially available, such as the Atlas Suntest TMXXL Equipment (Atlas Materials Testing Solutions, Chicago, IL, USA) and SUGA Environmental Testing Instruments, Super Xenon Weatherometer, SX75 (SUGA Testing Instruments Co., Ltd., Japan).

[0125] The sample can be evaluated by the change in sheet resistance over time under the test conditions specified in the test. The values ​​can be normalized to the initial sheet resistance to focus on the time evolution. Typically, the value for R / R0 or R t / R0 plots the time evolution, where R t is the time evolving sheet resistance measurement and R0 is the initial value of the sheet resistance.

[0126] Preparation of test samples

[0127] In the following example, according to Figure 5 and 6 The process shown in the figure prepares the structure, which illustrates the process of forming the test samples, and the test samples are subjected to the tests in the following examples. Figure 5 , schematically showing the coating of the first side of the substrate. The substrate is supplied with a polyethylene (PE) protective film. Before being placed in the coating machine, the PET film is laminated to the exposed side of the polyimide substrate, such as Figure 5 In the following examples, two different polyimide (PI) substrates are studied. Figure 5 As shown in the second step of , the PE protective film is removed by peeling off the PE film to expose the first surface for processing, and a commercial acrylate-based hard coating is applied to the substrate using slot coating, air drying and UV curing. After exposing the substrate surface for coating, the structure is placed in a coating device. Figure 5 As shown in the next step, a conductive ink containing a solvent, a polymer binder, and a fusion solution of a stable dispersion of silver nanowires (AgNWs) is applied to the cured hard coating using slot coating. The nanowire coating is air dried (with heated forced air) to form a fused metal nanostructured network. An acrylate overcoat solution is applied to the transparent conductive film using slot coating, then air dried and subjected to UV curing. After curing the overcoat, a PET protective film is laminated to the overcoat to form a release layer, as shown in FIG. Figure 5 as shown in the final step of

[0128] refer to Figure 6 , illustrating processing of the second side of the substrate. Figure 5 The product of the first side of the substrate shown in is wound on a roll. To process the second side, the roll is turned over and processed through the same equipment used to coat the first side. Figure 6 In the first step, the PET protective film covering the second surface of the substrate is peeled off to expose the second surface of the substrate. Figure 6As shown in the second step of , an acrylate-based hard coating is applied to the exposed surface of the polyimide substrate using slot coating, and the hard coating is then air-dried and subjected to UV curing. A conductive ink comprising a solvent having a stable dispersion of silver nanowires (AgNWs), a polymer binder, and a fusing solution is applied to the cured hard coating, and then air-dried to form a fused metal nanostructured network, as shown in Figure 6 The overcoat precursor solution is then applied to the transparent conductive film, which is then air-dried and subjected to UV curing. Figure 6 As shown in the final step of the process, a PE protective film is laminated onto the cured outer coating.

[0129] Examples 1 and 2

[0130] The examples provide reliability testing results for samples of two different optically clear adhesives having a hard coat primer between the substrate and the fused metal nanostructured network under elevated temperature and relative humidity testing conditions or under Xe illumination conditions.

[0131] In Examples 1 and 2, samples were prepared as described above using a 13 micron polyimide substrate from Damai that is transparent in the visible spectrum and blocks UV light. The optical and electrical properties of the films were measured twice and are summarized in Table 1 below.

[0132] Table 1

[0133] Resistor – PET side 52Ω / □ Resistor – PE side 48Ω / □ Transmittance 91.1% Turbidity 1.19% b* 3.12

[0134] The samples were also subjected to stability testing using a high temperature / high humidity test (85°C / 85% RH) and a Xe illumination test under two different test conditions. Figure 7 The structure shown was tested at 85°C / 85% RH. Figure 7 , 125 μm HC-PET films were applied to both sides of the structure using two different commercial optically clear adhesives: Example 1 - LG9052D and Example 2 - 3M8146-2. Examples 1 and 2 included a hard coating between the polyimide substrate and the fused metal nanostructured network on both sides of the polyimide substrate. The resistance over time (R / Ro) was measured over six hundred (600) hours using 85°C / 85% RH test conditions in a controlled test apparatus, and the time dependence of the resistance is plotted in Figure 8 middle.

[0135] In another set of tests, samples were subjected to Xe lamp test conditions. Fig. 9 The structure is tested with Xe lamp. Fig. 9 The structure is Figure 7A structure with half of its surface covered with Atlas Suntest TM Black tape in the XXL device. The conditions in the test device had a black standard temperature of 60°C (setting for the device), an air temperature of 38°C, a relative humidity of 50% and 60 W / m from a xenon lamp with a daylight filter. 2 (300nm to 400nm) irradiance. Fig. 9 Unless otherwise noted, the hard-coated PET back cover sheet was placed face up toward the lamp in the device and approximately half of the area was covered with black tape. For the Xe lamp test, R / Ro was measured over five hundred (500) hours and is plotted at Fig.10 middle.

[0136] For Examples 1 and 2, all samples passed the test under the test conditions, which was determined as R / Ro values ​​< 1.1 at the end of the test time.

[0137] Examples 3 and 4

[0138] The example tests the reliability of samples prepared under the test conditions without a hardcoat primer.

[0139] The coated substrates were prepared as described above in Examples 1 and 2, except that the placement of the hardcoat was omitted, and the test structures were then assembled. Fig.11 , the test samples of Examples 3 and 4 are similar in structure to the samples in Examples 1 and 2 ( Figure 7 ), except that there was no hard coat. A transparent conductive film was applied to both sides of the polyimide substrate, and an overcoat was applied to the transparent conductive film on each side. A PET protective film was applied to the overcoat on each side using two different optically clear adhesives: Example 3 - LG 9052D and Example 4 - 3M 8146-2. The resistance (R / Ro) using the 85°C / 85% RH test condition was measured over six hundred (600) hours and is plotted at Fig.12 middle.

[0140] For the xenon arc test, the Fig.13 The resistance (R / Ro) using the Xe lamp test condition was measured over a period of more than five hundred (500) hours and the results are plotted at Fig.14 In the Atlas Suntest TM The accelerated tests were performed in an XXL instrument (Atlas Materials Testing Solutions, Chicago, IL, USA). The conditions in the test instrument had a black standard temperature of 60°C (setting for the instrument), an air temperature of 38°C, a relative humidity of 50%, and a power of 60 W / m from a xenon lamp with a daylight filter. 2Unless otherwise noted, the hard-coated PET backing sheet was placed face up toward the lamp in the apparatus and approximately half of the area was covered with black tape.

[0141] For the samples, the R / Ro value under the 85°C / 85% RH test conditions failed to maintain a value below 1.2 at the end of the test. Under the Xe test conditions, only the sample with OCA-B met the goal of maintaining an R / Ro value below 1.2. The examples demonstrate the usefulness of a hardcoat primer coating for the substrate.

[0142] Example 5

[0143] This example tests the reliability of a double-sided conductive structure with a thin polyimide substrate from an alternative supplier without using a hard coat under the coating under the transparent conductor.

[0144] Samples were prepared using roll-to-roll processing as described above for a double-sided conductive structure as described above with a 15 μm thick transparent polyimide sheet from Kolon. Fig.15 and 16 , a transparent conductive film was applied to the Kolon CPI, and an overcoat was applied to the transparent conductive film, and a PET protective film was applied to the overcoat using an optically clear adhesive (flexible OCA from 3M). For Xe testing, Fig.16 As shown in , black tape is applied on half of the top surface.

[0145] The resistance (R / R0) using the 65°C / 90% RH test condition is measured over eight hundred (800) hours, and Fig.17 The resistance (R / R0) using the Xe light test condition was measured over one thousand (1000) hours and is plotted in Fig.18 In Atlas Suntest TM The accelerated tests were performed in an XXL instrument (Atlas Materials Testing Solutions, Chicago, IL, USA). The conditions in the test instrument had a black standard temperature of 60°C (setting for the instrument), an air temperature of 38°C, a relative humidity of 50%, and a power of 60 W / m from a xenon lamp with a daylight filter. 2 The irradiance of 100 nm to 200 nm was 100 nm. The hard-coated PET back cover sheet was placed face up toward the lamp in the apparatus, and approximately half of the area was covered with black tape, unless otherwise noted. A summary of the 65°C / 90%RH, 85°C / 85%RH testing is included in Table 2. For the samples, good test results were obtained without a hard coating in the structure.

[0146] Table 2

[0147]

[0148] Example 6

[0149] This example repeated the testing of Example 5 using the substrates of Examples 1-4.

[0150] The samples were prepared using roll-to-roll processing as described above for Figure 7 and 9 The double-sided conductive structure described in has a 13 micron thick transparent polyimide sheet from Damai. The structure has a flexible optically clear adhesive from 3M Company.

[0151] The resistance (R / R0) using the 65°C / 90% RH test condition is measured over eight hundred (800) hours, and Fig.19 The resistance (R / R0) using the Xe lamp test condition was measured over one thousand (1000) hours and is plotted in Fig. 20 The test was performed as described in Example 5. The stability results were outstanding.

[0152] The above embodiments are intended to be illustrative rather than restrictive. Additional embodiments are within the claims. In addition, although the present invention has been described herein with reference to specific embodiments, those skilled in the art will recognize that changes may be made in form and detail without departing from the spirit and scope of the present invention. Any inclusion of the above-referenced documents is limited so as not to include subject matter that is contrary to the explicit disclosure herein. With respect to the specific structures, compositions and / or methods described herein with components, elements, ingredients or other parts, it should be understood that, unless otherwise specifically indicated, the disclosure herein covers specific embodiments, embodiments comprising specific components, elements, ingredients, other parts or combinations thereof, and embodiments consisting essentially of the specific components, ingredients or other parts or combinations thereof, which may include basic features that do not change the basic properties of the subject matter as suggested in the discussion.

Claims

1. A double-sided conductive structure, comprising: a transparent polymer substrate comprising a polymer and having a first surface and a second surface, wherein the polymer substrate has an average thickness of no more than 27 micrometers, and the polymer in the configuration of the transparent polymer substrate has a transmittance of at least 88% at 400 nm to 750 nm and a transmittance of no more than 15% in the UV spectrum from 330 nm to 375 nm; first and second sparse metal conductive layers, supported on the first surface and the second surface of the transparent polymer substrate, respectively; and a polymer overcoat layer on each sparse metallic conductive layer, wherein the polymer overcoat layer has an average thickness of 10 nm to 200 nm, Each surface of the double-sided conductive structure has a sheet resistance of no more than 120 ohms / square.

2. The double-sided conductive structure according to claim 1 further comprises a first hard coating layer and a second hard coating layer, each having an average thickness of 50 nm to 3 microns, wherein the first hard coating layer is between the first surface of the transparent polymer substrate and the first sparse metal conductive layer, wherein the second hard coating layer is between the second surface of the transparent polymer substrate and the second sparse metal conductive layer, and wherein both hard coating layers comprise a cross-linked polyacrylate polymer. 3 . The double-sided conductive structure according to claim 2 , wherein each hard coating layer has a thickness of 100 nm to 2.5 microns and comprises highly cross-linked polyacrylate.

4. The double-sided conductive structure according to any one of claims 1 to 3, wherein the double-sided conductive structure can be assembled into a test structure having an optically clear adhesive and a 125 micron thick PET film on each surface, and subjected to an accelerated wear test for 500 hours at 85°C and 85% relative humidity, wherein the sheet resistance does not increase by more than 40%.

5. The double-sided conductive structure of any one of claims 1 to 3, wherein the polymer comprises polyimide.

6. The double-sided conductive structure of any one of claims 1 to 3, wherein the polymer substrate has an elongation of at least 10%, a tensile strength of at least 50 MPa, and a Young's modulus of 1.5 GPa to 7.0 GPa.

7. The double-sided conductive structure according to any one of claims 1 to 3, wherein the polymer comprises polysulfide, polysulfone, polyethylene naphthalate or polyethersulfone.

8. The double-sided conductive structure of any one of claims 1 to 3, wherein each sparse metal conductive layer comprises a fused metal nanostructured network and wherein the double-sided conductive structure can be repeatedly bent at least 200,000 times around a 1 mm diameter mandrel, wherein the sheet resistance of each sparse metal conductive layer changes by no more than 10%.

9. The double-sided conductive structure of claim 8, wherein the sheet resistance of each fused metal nanostructured layer does not exceed 100 ohms / square.

10. The double-sided conductive structure of claim 9, having a visible light transmittance of at least 88%, a haze of no more than 2.5%, and a b* value in the CIELAB color space of no more than 4.

0. The double-sided conductive structure according to claim 1 , wherein the first and / or second sparse metal conductive layer is patterned. 12 . The double-sided conductive structure according to claim 1 , wherein the first and / or second sparse metal conductive layers are independently patterned using UV light.

13. A method for forming a transparent conductive film, the method comprising: forming a first sparse metallic conductive layer supported on a first surface of a transparent polymer substrate, the transparent polymer substrate having an average thickness of no more than 27 micrometers, wherein the polymer substrate has a second surface supported on a first polymer release film; applying a polymeric outer coating layer onto said first sparse metallic conductive layer; placing a second polymeric release film on the polymeric outer coating; removing the first polymer release film to expose the second surface of the transparent polymer substrate; forming a second sparse metal conductive layer supported on the second surface of the transparent polymer substrate; and A polymeric overcoat is applied over the second sparse metallic conductive layer.

14. The method of claim 13, further comprising forming a cross-linked hard coating having an average thickness of no more than 3 microns between the polymer substrate and each of the first sparse metallic conductive layer and the second sparse metallic conductive layer. 15 . The method according to claim 14 , wherein the cross-linked hard coating layer is formed by irradiating with UV light and wherein the cross-linked hard coating layer comprises polyacrylate.

16. The method of any one of claims 13 to 15, wherein the first polymer release film comprises a polymer sheet having a glass transition temperature of at least 100°C.

17. The method of any one of claims 13 to 15, wherein each polymer outer coating is crosslinked using UV radiation.

18. The method according to any one of claims 13 to 15, wherein the first sparse metal conductive layer and the second sparse metal conductive layer are formed by: applying a conductive ink comprising silver nanowires dispersed in a solvent and a polymer binder to the first and second surfaces of the transparent polymer substrate, respectively; and The applied ink is dried to form the first and second sparse metal conductive layers.

19. The method of claim 18, wherein the conductive ink comprises a flux and wherein drying forms a fused metal nanostructured layer.

20. A transparent conductive film having an average thickness of no more than 30 micrometers and comprising: Transparent polymer films having an average thickness not exceeding 27 micrometers; first and second sparse metallic conductive layers on first and second sides, respectively, of the transparent polymer film; and a polymer overcoat layer on each sparse metallic conductive layer, wherein the polymer overcoat layer has an average thickness of 10 nm to 500 nm, wherein the transparent conductive film has a sheet resistance of no more than 100 ohms / square on each side, a %TT of at least 89%, a haze of no more than 2.5%, and a b* in the CIELAB color space of no more than 3.5, and The transparent conductive film can be assembled into a test structure having an optically clear adhesive and a 125 micron thick PET film on each surface and subjected to an accelerated wear test at 85°C and 85% relative humidity for 500 hours with no more than 40% increase in sheet resistance.

21. The transparent conductive film according to claim 20, further comprising a first hard coating layer and a second hard coating layer, each having an average thickness of 50 nm to 3 microns, wherein the first hard coating layer is between the first surface of the transparent polymer film and the first sparse metal conductive layer, wherein the second hard coating layer is between the second surface of the transparent polymer film and the second sparse metal conductive layer, and wherein both hard coating layers comprise a cross-linked polyacrylate polymer. 22 . The transparent conductive film according to claim 21 , wherein each hard coating layer has a thickness of 100 nm to 2.5 micrometers and comprises highly cross-linked polyacrylate.

23. The transparent conductive film of any one of claims 20 to 22, wherein the transparent conductive film can be assembled into a test structure having an optically clear adhesive and a 125 micron thick PET film on each surface and subjected to an accelerated wear test for 500 hours at 85°C and 85% relative humidity with no more than 20% increase in sheet resistance.

24. The transparent conductive film of any one of claims 20 to 22, wherein the polymer comprises polyimide.

25. The transparent conductive film of any one of claims 20 to 22, wherein the transparent polymer film has an elongation of at least 10%, a tensile strength of at least 50 MPa, and a Young's modulus of 1.5 GPa to 7.0 GPa.

26. The transparent conductive film of any one of claims 20 to 22, wherein the polymer comprises polysulfide, polysulfone, polyethylene naphthalate, or polyethersulfone.

27. The transparent conductive film of any one of claims 20 to 22, wherein each sparse metallic conductive layer comprises a fused metal nanostructured network and wherein the transparent conductive film can be repeatedly bent at least 200,000 times around a 1 mm diameter mandrel, wherein the sheet resistance of each sparse metallic conductive layer changes by no more than 10%.

28. The transparent conductive film of claim 27, wherein the sheet resistance of each fused metal nanostructured layer is no more than 75 ohms / square.

29. The transparent conductive film according to claim 28, having a visible light transmittance of at least 89%, a haze of no more than 2.5%, and a b* value in the CIELAB color space of no more than 4.0.